A novel two-dimensional transition metal dichalcogenide as water splitting photocatalyst with excellent performances - Wang, Fang; Cheng, Zishuang; Zhang, Xiaoming; Xie, Chunxiao; Liu, Fucai; Chang, Chuntao; Liu, Guodong (Frontiers in Chemistry, 2022)
With the rising demand for renewable energy, photocatalysts are considered the most promising solution to harness solar energy, and the search for photocatalysts with excellent performances remains an urgent task. Here, based on density functional theory (DFT), the photocatalytic properties of MoWS4 are systematically studied. The MoWS4 monolayer and bilayer turn out to be semiconductors with indirect band gaps of 2.01 eV and 1.48 eV. Moreover, they exhibit high and anisotropic light absorption coefficients of up to 105 cm-1 in the visible-ultraviolet region. Without any external adjustment, the band edge positions can fully satisfy the redox potentials. The electron mobility of MoWS4 monolayer is up to 557 cm2 V-1s-1, which is seven times higher than that of MoS2 monolayer. These results suggest that MoWS4 can be regarded as a promising 2-D photocatalyst candidate for water splitting.